THE IMMUNE SYSTEM OF THE RESPIRATORY TRACT AND ITS RELATIONSHIP WITH PULMONARY TUBERCULOSIS - Bomfim, Renata Oliveira Marques; de Sá, Kim Fonseca Gomes; Rocha, Aline Cristina; Júnior, Paulo Sérgio Soares (Seven Editora, 2024)
Tuberculosis is one of the oldest diseases of humanity, caused by bacteria belonging to the Mycobacterium tuberculosis complex. According to the World Health Organization, around 100 million people are infected each year with M. tuberculosis and, in underdeveloped countries, between 30% and 60% of them, adults are infected. A bibliographic review of specific literature was carried out to identify scientific articles in the MEDLINE, PubMed, and Scielo databases, published between 2018 and 2022, using the terms "Mycobacterium tuberculosis (M. tuberculosis), anatopathology, histopathology, and pathophysiological processes". The tuberculosis bacillus is transmitted by inhalation of infectious droplets dispersed in the air by an infected patient by coughing, sneezing, and talking. The importance of histological, anatomical, and immunological knowledge is crucial to guide the health professional towards the best care.DOI: https://doi.org/10.56238/sevened2024.037-076